An Enhanced Memory Address Mapping Scheme for Improved Memory Access Performance of 2-D DWT Processing Systems - Lee, Sze-Wei; Lim, Soon-Chieh (SPRINGER, 2007)
The implementation of the memory for storing image and transform coefficients in 2-D DWT processing systems using the more cost-effective external memory module such as DDR DRAM is shown to suffer from effective memory bandwidth which is significantly lower than the memory system peak bandwidth if the conventional direct logical-to-physical memory address mapping is adopted. The low effective memory bandwidth is caused by the high level of memory overhead cycle occurrence which is in turn is closely related to the logical memory access patterns of 2-D DWT processes. The problem becomes even more severe for the 2-D DWT processing of video. An analysis on the logical memory access patterns of multi-level 2-D DWT is carried out and an enhanced logical-to-physical memory mapping scheme which minimizes the occurrence of memory overhead cycles is proposed. The proposed scheme is simulated and its performance in terms of effective memory access bandwidth is evaluated and compared with the conventional direct mapping scheme.